2005
DOI: 10.1016/j.ejpain.2004.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Cough headache: frequency, characteristics and the relationship with the characteristics of cough

Abstract: Cough headache (CH) is a relatively rare, but an important complication of cough. The aim of this cross-sectional clinical study was to evaluate the frequency, characteristics and etiology of CH among the patients referred to our Outpatient Department with the complaint of cough, and to investigate the relationship between their cough and headache characteristics. We evaluated 96 females and 69 males, a total of 165 patients with cough. Among those, 57 patients (34.5%) had one or more cough complications and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…Other reported causes of symptomatic cough headache include carotid or vertebrobasilar diseases and cerebral aneurysms. Differently from PCH, secondary cough headache begins earlier (average 40 vs 60 years), is located posteriorly, lasts longer (years vs months), is associated with posterior fossa signs or symptoms, and does not respond to indomethacin [9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…Other reported causes of symptomatic cough headache include carotid or vertebrobasilar diseases and cerebral aneurysms. Differently from PCH, secondary cough headache begins earlier (average 40 vs 60 years), is located posteriorly, lasts longer (years vs months), is associated with posterior fossa signs or symptoms, and does not respond to indomethacin [9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…According to Özge et al, pain was mostly located in the frontotemporal regions but even toothache as the presenting symptom has been described [9,10]. It most often affects men, however, Pascual et al reported on 28 patients with primary cough headache, of which 18 were women [11].…”
Section: Cough Headachementioning
confidence: 99%
“…General consensus exists that the treatment of choice for primary cough headache is indeed indomethacin, however with varying daily doses, treatment durations and treatment effects with a general response rate of approximately 73% [3]. Several studies found that daily doses ranging from 25–150 mg usually are effective [3,9,11,13,31]. In one study a daily dose up to 250 mg was required [24].…”
Section: Cough Headachementioning
confidence: 99%
See 1 more Smart Citation
“…It is exclusively triggered by coughing, pressing or other types of Valsalva maneouvres. In 11% to over 50% of the cases, the headache triggered by coughing is a symptomatic headache [18–21]. The most frequent cause of a symptomatic cough headache is an Arnold‐Chiari malformation type I.…”
Section: Primary Cough Headache (Ihs 42)mentioning
confidence: 99%